2000
DOI: 10.1046/j.1365-2125.2000.00201.x
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants in the elderly: challenges for study design and their interpretation

Abstract: Drug treatment of depressive illness in the elderly differs from that in younger patients and there is no clear consensus as to ®rst line treatment in the former. Nor is it possible to extrapolate directly from studies in younger patients to the elderly with these agents. Whilst there are over two dozen antidepressants currently marketed in the U.K., most studies have been on younger adults and have excluded very old and frail patients. Design short-comings of the few trials conducted in elderly patients do no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
0
16
0
1
Order By: Relevance
“…The efficacy of antidepressant treatment was unconfirmed for that patient population. Parikh (2000) summarized the challenges in study design and result interpretation for evaluating the efficacy of antidepressant treatment in older adults [21]. Most Phase II and III clinical trials on antidepressants had been on younger adults and excluded very old and frail patients.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of antidepressant treatment was unconfirmed for that patient population. Parikh (2000) summarized the challenges in study design and result interpretation for evaluating the efficacy of antidepressant treatment in older adults [21]. Most Phase II and III clinical trials on antidepressants had been on younger adults and excluded very old and frail patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the inclusion of at least 25% of subjects aged 75 years and over in studies of drugs that will be registered for use in the elderly. Due to the fact that the majority of studies of antidepressants use a highly selective trial population, without signifi cant co-morbidity and with minimum numbers of elderly subjects, there are fundamental problems extrapolating the results to the elderly population as a whole (Parikh 2000). However, despite the lack of evidence, there are some recommendations in the literature relating to the use of antidepressants in the elderly.…”
Section: Antidepressantsmentioning
confidence: 95%
“…However, despite the lack of evidence, there are some recommendations in the literature relating to the use of antidepressants in the elderly. It is widely reported that older patients are more prone to side-effects and have greater diffi culty tolerating doses of antidepressants that are likely to be of therapeutic value (Parikh 2000;ANZCA 2005). Older adults often require lower initial doses with slow titration and the initial dose should be one-half or lower than the normal starting dose (Antai-Otong 2006).…”
Section: Antidepressantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Es sind Studien bei älteren Patienten vonnöten, um optimale Dosen, z.B. von Antidepressiva, zu ermitteln (4). Folge ist häufig eine Anwendung von Medikamenten außerhalb der Zulassung ("off-label-use"), so z.B.…”
Section: Klinische Studien An Alterspatientenunclassified